Features of labor activity during a pandemic and its impact on the economy in Ukraine - Serohina, Nataliia; Petryshchenko, Nataliia (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The COVID-19 pandemic has significantly altered the way the global labor market works. Labor activity during the pandemic is increasingly moving into the field of digitalization and electronic lifestyles. This trend has led to significant changes in the quality of the population’s life, as well as in the economic activities of manufacturers and sellers. This demonstrates the need for a more detailed study of trends in the development of the labor market and potential changes in the employment of labor resources. Some of the main structural components affecting the state of the country’s economy in a pandemic are highlighted. For the analysis, this includes the level of employment and the change in the profile of labor resources, as well as the income and losses of the country’s enterprises, and the GDP dynamics. This choice is due to the fact that labor resources are the productive force of the enterprise, which affects the efficiency of activities and profitability. In the existing conditions, the search for opportunities to improve the current order of labor organization is becoming relevant. The purpose of the article is to determine the main trends in the development of the Ukrainian economy, taking into account the negative impact of the pandemic, to identify the dynamics in the composition of the country’s labor resources, and to propose possible ways to reduce the negative consequences of lockdowns and production interruptions. The factor of profitability of the production spheres, which determines the socio-economic development of the state, is also considered. Depending on this factor, disproportions are formed at the levels of socio-economic development. Based on the data of state statistics and using the methods of empirical and mathematical research, the analysis of the dynamics of the main indicators has been carried out. Based on the data obtained on the sphere of work and financial performance of enterprises for 2020, an economic diagnostics of their unprofitableness was carried out. The method of horizontal and vertical analysis revealed a decrease in the employed population of the country, an increase in the unemployment rate, and a decrease in GDP. Calculations of the dynamics and structure of incomes and losses of Ukrainian enterprises made it possible to identify the most unprofitable sectorsof the economy. In most cases, a change in the organization of work leads to the adaptation of the activities of the enterprise, taking into account certain conditions. The transfer of part of the workforce to work using remote methods allows not to stop production and support the country’s economy with the introduction of quarantine (lockdown). This serves as an adequate alternative compared to the prospect of dismissal of workers, which will affect not only the financial security of the population, but also the profitability of production spheres. In a pandemic, filling the budget is extremely important. This will allow funding to support entrepreneurship, vaccinations and social security for most of the population. Digitalization and remote work are a promising area that will take a significant place in the organization of work in the future. The main task of the state should be to create algorithms and standards for the social protection of people, as well as state support of enterprises.
Keywords: labor resources; digitalization; pandemic; profitability; social security